REPRESENTASI KESETARAAN GENDER DALAM FILM MULAN (Analisis Semiotika Roland Barthes film Mulan) - Ariyan Alfraita; Tira Fitria Wardhani; Julyanto Ekantoro (Pusat Studi GESI - UWP, 2022)
Films are often considered only as a medium for entertainment purposes, but films can also display hidden messages according to the wishes of the creators, including the Disney film Mulan which was broadcast simultaneously throughout the world via Disney Plus Hotstar 4 September 2020 streaming application. in it some messages carry the theme of gender equality, which is still a controversial issue in several parts of the world, including in China, the setting of the place where Mulan's film is told, this research will analyze symbols containing messages representing gender equality in the film Mulan with Roland Barthes' semiotic approach, and as a result, Mulan's film contains symbols of gender equality. This Disney film carries the message that men and women should be given equal opportunities in any case, including defending the country on the battlefield.